Ketahanan Sosial dan Kesejahteraan Lintas Generasi di Kampung Kota: Analisis Empiris Kesehatan Lansia dan Pencegahan Stunting di Kampung Lio, Depok - Sri Murni; Irhamni Rahman (Pusat Riset dan Inovasi Nasional, 2025)
This study explores the interplay between aging, maternal care, and community health within an urban kampung setting, focusing on Kampung Lio, Depok City. With rising urbanization pressures, marginalized communities like kampungs face compounded challenges to health equity, particularly for vulnerable populations such as older adults and young children. The research aims to assess the physical and mental well-being of older adults and evaluate the knowledge, attitudes, and practices (KAP) of mothers regarding stunting prevention, emphasizing the role of community-based interventions. A mixed-methods approach was employed, combining structured surveys of 16 elderly individuals and 13 mothers of children under five, with data analyzed through descriptive statistics and thematic analysis. Findings reveal that while elderly residents face significant socioeconomic and physical vulnerabilities, their quality of life remains resilient, largely supported by close familial bonds and cohesive community networks. Mothers exhibit strong awareness and positive attitudes toward stunting prevention, demonstrating a high level of knowledge about nutrition and child development. However, practical implementation of optimal feeding practices is hindered by systemic constraints such as financial limitations, time scarcity due to work or caregiving burdens, and limited access to nutritious food sources. The study underscores the importance of integrated, locally grounded strategies that strengthen intergenerational support systems, empower caregivers, and address structural barriers within urban informal settlements. These insights highlight the critical role of community health initiatives in enhancing social resilience and improving long-term health outcomes in dense, resource-constrained urban environments.